Eastern Caribbean Currency Union : 2018 Discussion on Common Policies of Member Countries-Press Release; Staff Report; and Statement by the Executive Director for the Eastern Caribbean Currency Union. (IMF Staff Country Reports; Country Report ;, 2019)
This 2018 discussion on common policies of the Eastern Caribbean Currency Union (ECCU) highlights that the member countries are gradually recovering following the catastrophic impact of Hurricanes Irma and Maria in 2017. Conditions remain favorable to growth, however, risks are increasing. The fiscal balance for the region as a whole worsened in 2017, reflecting lower inflows from citizenship-by-investment programs and higher reconstruction and current spending. The IMF team made several policy recommendations including shifting focus from the current emphasis on recovery from natural disasters to building ex-ante resilience. The report also recommends intensifying decisive and timely actions to resolve weaknesses in the financial sector, including longstanding problems in the banking sector and emerging risks in the non-banking sector. The authorities expressed commitment to the acceleration of key reforms to upgrade and strengthen the financial sector regional oversight framework. In addition to fiscal consolidation, injecting new vigor into the structural policy agenda will help enhance competitiveness and make growth more inclusive.